CpG-oligodeoxynucleotides in chronic rhinosinusitis cell culture - Birk, Richard; Aderhold, Marc Christoph; Hörmann, Karl; Schell, Angela; Kramer, Benedikt; Eschenhagen, Till; Sommer, Ulrich (In vivo, 2016)
In chronic rhinosinusitis (CRS) an important feature is the infiltration of eosinophils, triggered by T-helper type 2 cells (TH2). Binding of the CpG oligodeoxynucleotide (CpG-ODN) ligand to toll-like receptor 9 (TLR9) induces a shift from a TH2- to a TH1-type response. We evaluated the hypothesis that CpG-ODN could reduce the predominantly TH2-driven response in our cultures. Materials and Methods: Twenty samples from CRS patients with (CRSwNP) and without nasal polyposis (CRSsNP) were cultivated. The expression of interleukin 5 (IL-5), eotaxin 3 and matrix metalloprotease 9 (MMP-9) were evaluated with and without CpG-ODN. Results: Addition of CpG did not influence the expression of IL-5 and eotaxin-3 DNA. Elevated MMP-9 expression in cultures from CRSwNP and CRSsNP patients could be established. Conclusion: CpG does not reduce the attraction of eosinophils since no reduced IL-5 expression was measured in our cultures. Yet, MMP-9 - an important factor in tissue remodelling - was elevated in cultures from CRS patients.